Evaluation of Different Methods for Total DNA Extraction from Sago Pith Residue - Azham, Zulkharnain; Norhafizah, Sidek; Awang Ahmad Sallehin, Awang Husaini (Hibiscus Publisher, 2014)
Direct extraction of DNA from the environment has become major importance for molecular analyses for the study of microbial communities in soil and other decomposing agrowaste. The presence of humic substances in Sago pith residue not only results in low DNA quality but also can lead to PCR amplification inhibition which may hinder most molecular studies. Many of the published protocols have been found to be unsuitable to obtained high amount of yield and low of humic acids contamination. This study presents the evaluation of three different methods for extracting total DNA from Sago pith residue. The methods evaluated were enzymatic lysis, glass bead homogenization and freeze-thaw treatment. Each method were evaluated by 260/280 nm absorbance ratio for protein contamination, 260/230 nm absorbance ratio for other contaminants and PCR amplification for molecular work suitability. Among the three methods, freeze-thaw treatment provided the highest yield of DNA, 5.06±0.01 μg/g of Sago pith residue. Nevertheless, all three methods resulted in poor DNA quality which could be used for PCR amplification. Additional steps of agarose electrophoresis and silica column purification were found to be effective for increasing the equality of the extracted DNA and were validated by positive PCR amplifications